Penyakit Dan Kelaparan: Telaah Perkataan Yesus Dalam Lukas 21:11 Dan Relevansinya Bagi Gereja Di Masa Pandemi Covid-19 - Stephano Ambesa (Bethel Press, 2020)
This paper is a library research that uses library material as a source of data, to examine Jesus' Words in Luke 21:11 about illness and hunger and find their relevance to the Church in the Pandemic Period. The primary data source in this study is the Gospel of Luke 21:11 which is exposition by the author, supported by secondary data sources namely documents, books and references that are relevant to the problems in this study, and see the current condition of the Covid-19 pandemic. The results of this study suggest how the attitude should be taken by the Church in the midst of the Covid-19 pandemic: First, the church must be happy because it understands why illness and hunger are